Pelaksanaan Program Pusaka Sakinah dalam Pandangan Hukum Islam (Studi Kasus di KUA Kecamatan Palang Kabupaten Tuban) - Karmuji Karmuji; Muhyidin Muhyidin (JOSH: Journal of Sharia, 2022)
Implementation of the Sakinah Heritage Program in the View of Islamic Law (Case Study at KUA Palang District, Tuban Regency)” This is the result of field research that aims to answer questions about how to implement the Sakinah heritage program in KUA Palang District and how to analyze Islamic law on the implementation the sakinah heritage program at the KUA in Palang District.This research is a qualitative field research. The data in this study were obtained through observation, interviews, and documentation, and then processed and analyzed using descriptive analysis techniques and deductive thinking patterns.From the results of the study it can be concluded that the guidance of Pusaka Sakinah at the Office of Religious Affairs (KUA) of Palang District is carried out after the marriage, which is carried out for two days using the "Blessings (Learning Secrets of Marriage) module to Build Harmonious Relationships" which consists of Marriage Guidance, Relationships Healthy, and Family Economy. The Sakinah Heritage Program is in accordance with Islamic law, namely in terms of building a sakinah family which is the goal of marriage to have a peaceful and peaceful family. It is hoped that the Ministry of Religion will work even harder in implementing the Sakinah Heritage guidance program which has just been launched, hopefully in the future this program can be implemented effectively in Religious Affairs Offices (KUA) throughout Indonesia in facilitating and providing guidance and consultation on family problems so that later it will be realized in accordance with the purpose of the Sakinah Heritage program. For guidance participants, they should follow the guidance process properly so that they really get maximum results/knowledge. So that the results of the guidance can be used as a reference and guide during domestic life.